Laboratories Investigation on Creep Stiffness of Aphalt Mixture Incorporating Steel Fibre - Vengadasalapathey, Logiswaran; Mohamad Taher, Mohammad Nasir (Recent Trends in Civil Engineering and Built Environment, 2023)
Flexible pavement is the most common type of pavement found on Malaysian roads. The three most common types of pavement failure are rutting, fatigue cracking, and thermal cracking. The focus of this research was to develop asphalt mixture for flexible pavement based on the JKR/SPJ/2008 standard specification and it is regarding asphalt mixture incorporating with steel fibre. The objectives of this study were to investigate the properties of asphalt binder, aggregates, and steel fibre in HMA mixture and to evaluate the creep stiffness of fibre reinforce asphalt mixtures. The properties of steel fibre, aggregate and asphalt binder were characterised according to the standard and specification AASHTO, ASTM and JKR and the performance of the steel fibre asphalt mixture was tested using dynamic creep test. The expected outcome of the study was to determine the deformation of the asphalt mixture when it is mix with the steel fibre according to the percentage of the mixture, reduce rutting and improve the strength of pavements using steel fibre (SF) as a reinforcement. and expected to benefit the future of flexible pavement in Malaysia, as well as aid in the development of the use of asphalt mixtures with steel fibre in road construction in Malaysia, as per the JKR standard.